Community Benefits for Hamilton LRT - Mohammad, Sana; Ahmed, Rabeeyah; Butt, Nadia; Elgamal, Raghd (Prepared by the McMaster Research Shop for Hamilton Community Benefits Network, 2022)
The Hamilton Community Benefits Network (HCBN) advocates for the use of Community Benefit Agreements (CBAs) in major city infrastructure projects. CBAs are agreements between governments, developers and coalitions of community organisations that address a range of community concerns and needs, including (but not limited to) ensuring residents benefit from major developments. In particular, the HCBN believes CBAs are a way to mitigate the impact to local communities by large scale infrastructure projects. The HCBN approached McMaster Research Shop to help conduct community focus groups and to analyse a community survey identifying priority areas and ideas for a CBA for the Hamilton LRT. This report provides a summary of the feedback.
Keywords: Hamilton, community-engaged research, community benefits, LRT, community consultation